Rhinovirus-induced PBMC responses and outcome of experimental infection in allergic subjects - Parry, David E.; Busse, William W.; Sukow, Kris A.; Dick, Claire R.; Swenson, Cheri; Gern, James E. (Journal of allergy and clinical immunology, 2000)
Background: The immune response to rhinovirus (RV) infections is considered to contribute to upper respiratory symptoms and may also be an important contributor to lower airway dysfunction in patients with asthma. Objective: This study was conducted to determine the relationship of RV-specific responses in PBMCs to the outcome of experimentally induced infection with RV16. Methods: Twenty-two subjects with either allergic rhinitis or asthma were inoculated with RV16: virus-induced proliferation and cytokine production were determined on PBMCs obtained before and then again 7 and 28 days after inoculation. Results: Several subjects had proliferative responses to RV16 before inoculation, and precold RV-specific proliferative responses were inversely correlated (rs = –0.62, P < .005) with RV shedding after inoculation. In addition, there was a negative correlation (rs = –0.58, P = 0.01) between precold RV-induced IFN-γ secretion ex vivo and peak RV shedding during the cold. Conclusions: Certain RV-specific lymphocyte responses before the cold (vigorous proliferation or IFN-γ secretion) were associated with reduced viral shedding after inoculation. These findings suggest that variations in mononuclear cell responses to RV could contribute to the individual variability in viral shedding during experimentally induced, and perhaps naturally acquired, RV infections in subjects with respiratory allergy or asthma. (J Allergy Clin Immunol 2000;105:692-8.)